The Relevance of Financial Statements in the Industrial Revolution 4.0 Era - Haryani Chandra; Chandra Ferdinand Wijaya (Binus Business Review, 2021)
The emergence of Industrial Revolution 4.0 has a significant impact on the business processes. It is also expectedto change the characteristics of the needed accounting information. The close ties between accounting and theIndustrial Revolution 4.0 encourages researchers to conduct research regarding the correlation between the twofields. The research aimed to discuss the characteristics of companies in the Industrial Revolution 4.0 era andidentify whether a mismatch occurred between the information in the financial statements and the changes inthe characteristics of companies in the Industrial Revolution 4.0 era. It was a narrative literature review usingsecondary data from various sources. Data collection was made through library research. Then, the data wereanalyzed using content analysis. The results show that more and more digital-based companies emerge and developwith a remarkably high company value even without having any underlying asset. On the other hand, severalstudies indicate that assets as an element of financial statements are necessary for determining the company valuefor allocating economic resources effectively. However, some studies explain that companies with high assetshave a high company value. It shows a gap that makes the relevance of financial statements in determining thecompany value in the Industrial Revolution 4.0 era questionable. This matter has implications for stakeholders touse financial statements for decision-making in Industrial Revolution 4.0 era and future research.